Proses Derivasi pada Adjektiva Emosi ‘Marah’ dalam Bahasa Indonesia (Studi Kasus: Korpus Leipzig) - Ida Ayu Vivin; Ni Kadek Aristyawati; Arjun Priyatama Kusuma; Fitria Marinda; Griffed Estonia Menanti (Udayana University, 2026)
Derivation is a morphological process that enriches vocabulary through affixation, particularly prefixation and suffixation, which may change both grammatical category and meaning. This study examines the derivational processes of the emotional adjective marah (“angry”) in Indonesian using data from the Leipzig Corpus. The data were analyzed with AntConc and SketchEngine through morphosemantic and syntactic analyses within a qualitative descriptive approach. The study aims to explain how marah undergoes derivation and how its derived forms function syntactically in Indonesian, especially from a linguistic typology perspective. The findings reveal patterns of morphological productivity and semantic variation in the derivation of emotion-related words. In term of linguistic, , this study contributes to a deeper understanding of adjective-based derivation in Indonesian, while theoretically it offers insights for typological morphology and corpus-based lexicographic research.